Pengaruh Kepemimpinan Transformasional, Pengawasan dan Komunikasi terhadap Kepuasan Kerja Pegawai pada Kantor Radio Republik Indonesia Malang - Sukoyo, Agus; Alhabsy, Taher (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2013)
This study aimed to describe transformational leadership, supervision, communication, and employee job satisfaction at RRI Malang; analyze and explain the effect of transformational leadership variables, control, communications simultaneously on employee satisfaction RRI Malang; as well as analyze and explain variable effect of transformational leadership, supervision, communication partially on employee satisfaction RRI Malang. Method in this study used a quantitative approach with type of research was description. Through this study, researchers wanted identifies the relationship or the effect of the studied variables and test the hypotheses that have been formulated. The results concluded: the descriptive statistical analysis of the transformational leadership (X1), supervision (X2) and communication (X3) note that all indicators of these variables are good and as expected. Based on the results of statistical analysis inferential test multiple linear regression can be seen that there is a simultaneous effect between three variables with the value of contribution of 15.8% and the remaining 84.2% are influenced by variables other than the independent variable studied. Based on the results of inferential statistical analysis with multiple linear regression analysis, there was the influence of three variables on employee job satisfaction (Y) partially.